Uncovering the Map of Poverty in the South Coast Region of East Java: A New Perspective from Spatial Analysis - Khoirul Ifa (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2025)
Poverty alleviation remains a global challenge and a key pillar of the sustainable development agenda. Unlike previous studies that generally examine poverty in aggregate or without considering spatial linkages, through the incorporation of socioeconomic and environmental dimensions into the Spatial Durbin Model (SDM), this research introduces a novel approach to investigating spatial interdependencies of poverty across the South Coast of East Java Province. The analysis using Spatial Weighting Matrix, Moran Index Analysis, Terting the significance of Spatial Parameters, Spatial Panel Model and Goodness of Fit Criteria that poverty in one locality is substantially shaped by the socioeconomic conditions prevailing in adjacent areas. The results show that economic growth and natural resource exploitation has a positive significant on poverty. This suggests that growth and resource exploitation do not necessarily reduce poverty. Conversely, accessibility has a negative and significant effect, confirming that increased connectivity can reduce poverty disparities between regions. Education, unemployment, and health factors show weaker or insignificant effects, although their spatial interactions remain important. The synthesis of these findings confirms that poverty in coastal areas is not merely a local issue, but a spatially contagious phenomenon. The practical implication of this research highlights the necessity of spatial-based policies that fast prioritize inclusive growth, equitable resource allocation, and the development of strategic infrastructure in order to break the cycle of poberty while maximizing positive splillover effects. Thus, this research not only enriches the literature on spatial economics but also provides concrete policy direction for accelerating poverty alleviation in line with sustainable development goals.